2011
DOI: 10.1016/j.crhy.2011.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Coupled study by TEM/EELS and STM/STS of electronic properties of C- and CNx-nanotubes

Abstract: Carbon nanotubes are the focus of considerable research efforts due to their fascinating physical properties. They provide an excellent model system for the study of one dimensional materials and molecular electronics. The chirality of nanotubes can lead to very different electronic behaviours, either metallic or semiconducting. Their electronic spectrum consists of a series of Van Hove singularities defining a bandgap for semiconducting tubes and molecular orbitals at the corresponding energies. A promising w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
(110 reference statements)
0
8
0
Order By: Relevance
“…This is to enable the electrons to flow to/from a STM tip. The STM images of CNTs can be very much depending on the curvature radius of the tip, CNTs diameter, and the different chiralities exhibited by the CNTs itself [113]. Consequently, the attachment of functional groups to the surface of CNTs and the mechanical stability of the bonding can also be analyzed using STM [112].…”
Section: Imaging Microscopies: Sem Tem Stem Afm and Stmmentioning
confidence: 99%
“…This is to enable the electrons to flow to/from a STM tip. The STM images of CNTs can be very much depending on the curvature radius of the tip, CNTs diameter, and the different chiralities exhibited by the CNTs itself [113]. Consequently, the attachment of functional groups to the surface of CNTs and the mechanical stability of the bonding can also be analyzed using STM [112].…”
Section: Imaging Microscopies: Sem Tem Stem Afm and Stmmentioning
confidence: 99%
“…Indeed, a clear and unambiguous proof of identification of individual dopants (N atoms in this case) in single-walled nanotubes has not yet been obtained, in contrast to the case of 2D materials (25), and the question remains whether electron microscopy is able to identify individual dopant atom configurations in such complex non-planar and beam-sensitive architectures. Here, we have carried out such experiments on single-walled, nitrogen-containing carbon nanotubes (CN x -SWNTs) synthesized via a laser vaporization technique (8,26). We clearly demonstrate the feasibility of dopant identification in a nanotube at the single-atom level.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning tunneling microscopy (STM) and spectroscopy (STS) are local techniques for studying the structural and electronic features/properties of materials. Indeed, some studies have been reported on CN x -NT (7)(8)(9) and recently also on N-doped graphene (10,11). However, chemical characterization cannot be unambiguously performed from the STM/STS analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Doping singlewall carbon nanotubes has also been considered. [9][10][11] Recent STM-STS experiments of N-doped graphene 5,8 have demonstrated the occurrence of chemical substitution. These experiments provide us with a detailed and local analysis with sub-atomic resolution of the electronic properties of the doped material.…”
Section: Introductionmentioning
confidence: 99%